(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Ensuring the confidentiality and privacy of patient information in healthcare interactions is not just a legal requirement but a fundamental element of ethical and effective patient care. These principles play a pivotal role in shaping the relationship between patients and healthcare providers, impacting trust, open communication, and the overall quality of healthcare delivery. In today’s healthcare landscape, the recognition of safeguarding patient information has grown, driven by a convergence of legal, technological, and societal factors. As healthcare systems evolve, striking a delicate balance between the necessity for information sharing and the obligation to protect personal data becomes increasingly intricate. This study delves into the various aspects of patient awareness, attitudes, and trust related to privacy and confidentiality in the healthcare setting. Focusing on the Medical Outpatient Departments (MOPD) at Lagos University Teaching Hospital (LUTH), the research aims to provide nuanced insights into the factors that influence patient perceptions. Understanding these dynamics is essential not only for enhancing patient-centered care but also for guiding educational strategies and shaping policy development